2021
DOI: 10.1039/d1ra07762g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kaolinite layer expansion and impurities on the solid-state reaction of kaolinite

Abstract: Effects of kaolinite layer expansion and impurities on the rapid formation of metastable CaAl2Si2O8 with the supression of byproduct formation were demonstrated based on the solid-state reaction of calcium carbonate with methoxy-modified kaolinite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 45 publications
7
43
0
Order By: Relevance
“…In our previous studies, 7,9 the kaolinite grinding process was found to generate new hydroxyl groups by breaking Al-O-Si bonds 7 and the expanded kaolinite increased the available edge surfaces. 9 The present immersion method could therefore be an effective means of doping the ground mixture of Ex-Kaol and CaCO 3 . Because the ground raw material exhibited some green phosphorescence aer immersion in the Tb 3+ solution (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…In our previous studies, 7,9 the kaolinite grinding process was found to generate new hydroxyl groups by breaking Al-O-Si bonds 7 and the expanded kaolinite increased the available edge surfaces. 9 The present immersion method could therefore be an effective means of doping the ground mixture of Ex-Kaol and CaCO 3 . Because the ground raw material exhibited some green phosphorescence aer immersion in the Tb 3+ solution (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…13 The raw materials and grinding conditions used in this research were identical to those employed in our previous study. 9 The kaolinite raw material was expanded Kanpaku kaolinite (JCSS-1101c, obtained from the Clay Science Society of Japan) without impurities (referred to herein as Ex-Kaol), a methoxy-modified kaolinite. 9 This material was used to rapidly generate metastable CaAl 2 Si 2 O 8 containing minimal byproducts (referred to herein as m-CAS).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations